Imaging with ultrasound contrast agents: current status and future - Chong, Wui K.; Papadopoulou, Virginie; Dayton, Paul A. (Abdominal imaging, 2018)
Microbubble ultrasound contrast agents (UCAs) were recently approved by the Food and Drug administration for non-cardiac imaging. The physical principles of UCAs, methods of administration, dosage, adverse effects, and imaging techniques both current and future are described. UCAs consist of microbubbles in suspension which strongly interact with the ultrasound beam and are readily detectable by ultrasound imaging systems. They are confined to the blood pool when administered intravenously, unlike iodinated and gadolinium contrast agents. UCAs have a proven safety record based on over two decades of use, during which they have been used in echocardiography in the U.S. and for non-cardiac imaging in the rest of the world. Adverse effects are less common with UCAs than CT/MR contrast agents. Compared to CT and MR, contrast-enhanced ultrasound has the advantages of real-time imaging, portability, and reduced susceptibility to metal and motion artifact. UCAs are not nephrotoxic and can be used in renal failure. High acoustic amplitudes can cause microbubbles to fragment in a manner that can result in short-term increases in capillary permeability or capillary rupture. These bioeffects can be beneficial and have been used to enhance drug delivery under appropriate conditions. Imaging with a mechanical index of < 0.4 preserves the microbubbles and is not typically associated with substantial bioeffects. Molecularly targeted ultrasound contrast agents are created by conjugating the microbubble shell with a peptide, antibody, or other ligand designed to target an endothelial biomarker associated with tumor angiogenesis or inflammation. These microbubbles then accumulate in the microvasculature at target sites where they can be imaged. Ultrasound contrast agents are a valuable addition to the diagnostic imaging toolkit. They will facilitate cross-sectional abdominal imaging in situations where contrast-enhanced CT and MR are contraindicated or impractical.